2020
DOI: 10.1016/j.parint.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and resistance of different artemisinin-based combination therapies: a systematic review and network meta-analysis

Abstract: Background: Malaria parasites have developed resistance to most of the known antimalarial drugs in clinical practice, with reports of artemisinin resistance emerging in South East Asia (SEA). We sort to find the status of artemisinin resistance and efficacy of different modalities of the current artemisinin-based combination therapies (ACTs). Methods: We carried out a systematic search in 11 electronic databases to identify in vivo studies published between 2001 and 2017 that reported artemisinin resistance. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 39 publications
(56 reference statements)
0
41
0
Order By: Relevance
“…Although cases of malaria have decreased by an estimated 20 million since 2010 [1], there was no significant progress in reducing the number of global cases from 2015 to 2017 [1]. Current efforts to prevent malaria mainly include preventive and symptomatic treatment with antimalarial compounds, consisting of artemisinin-based combination therapies [2], as well as vector control with long-lasting insecticidal mosquito nets (LLINs) and indoor residual spraying (IRS) [3], [4]; these methods have resulted in reductions in case incidence and mortality. However, increasing evidence has revealed that these efforts can only go so far [1], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although cases of malaria have decreased by an estimated 20 million since 2010 [1], there was no significant progress in reducing the number of global cases from 2015 to 2017 [1]. Current efforts to prevent malaria mainly include preventive and symptomatic treatment with antimalarial compounds, consisting of artemisinin-based combination therapies [2], as well as vector control with long-lasting insecticidal mosquito nets (LLINs) and indoor residual spraying (IRS) [3], [4]; these methods have resulted in reductions in case incidence and mortality. However, increasing evidence has revealed that these efforts can only go so far [1], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, cases of Chloroquine resistance were recorded in Southwest Asia and then in South America ( Nevin and Croft, 2016 ; Wongsrichanalai et al, 2002 ). Due this fact, since 2001, combined therapy with artemisinin (ATC) has been used in the treatment of malaria ( Su and Miller, 2015 ); however, failed treatments with ATC have been reported in strains of P. falciparum on the Thailand-Cambodia and Myanmar border, reaffirming the need for studies of new molecules with antiplasmodial potential ( Ashley et al, 2014 ; Bhumiratana et al, 2013 ; Mathenge et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such limitations led to the emergence of an innovative combination therapy approach based on multi-drug delivery nanocarriers with increasing benefits in diverse diseases, notably cancer (34,35). Although still in an early stage in the treatment of infectious diseases (36), the carrier-mediated multiple drug approach proved promising in the treatment of malaria (37,38).…”
Section: [Le1] [Le1]mentioning
confidence: 99%